Embankment on Pile: Performance Comparison of Bamboo and Mini Pile For Settlement Reduction and Stabilization of Embankment Over Soft Soil - Kevin, Paulus (Himpunan Ahli Teknik Tanah Indonesia, 2025)
Indonesia’s soft soil spreads across islands and it becomes one of the current challenges for newly constructed and existing infrastructure, particularly highways. To construct over it, consolidation and lightweight material methods have been utilized, however, this study will only discuss the embankment on pile method using bamboo cluster piles or mini piles. Based on finite element method (FEM) analysis, the embankment on the bamboo piles or mini piles can reduce settlement and increase the stability of the embankment. In a 30 cm-diameter bamboo cluster pile case, the settlement is reduced as the length/spacing (l/s) ratio increases and the safety factor also increases as the l/s ratio is higher. In terms of the mini pile case, it also has a similar trend where the settlement decreases as l/s increases, although this method has a lower settlement than bamboo. Also, the safety factor using mini pile in a similar l/s ratio is slightly higher than bamboo due to the significant differences in material properties. However, the bamboo material prospect is promising as this material is more sustainable with a smaller carbon footprint to construct than the mini pile counterpart.